2004
DOI: 10.1007/s10527-005-0005-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of noise correlation in channels of a digital X-ray detector—converter on evaluation of detection quantum efficiency

Abstract: A digital X-ray detectorconverter converts X-ray radiation energy passing through a patients body into digital signal. The device can use direct or indirect conversion. In the former case, the electric charge induced in the sensitive area of the detector as a result of radiation absorption is measured. This method is used in gas or solid-state ionization chambers and selenium-based detectors. In the latter case, the energy of gamma quanta is converted to energy of another type (for example, light energy), whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 2 publications
(5 reference statements)
0
4
0
Order By: Relevance
“…Correlation of output detector sig nals corrupts variance of output noise provided that special measures were not observed. It was suggested in [4] to divide open field image of interest into subdomains, deter mine mean brightness in subdomains, and calculate vari ance of mean brightness in subdomains. Mean brightness in subdomains is used to calculate system output noise variance.…”
Section: Estimate Of Scattering In Detector Channelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Correlation of output detector sig nals corrupts variance of output noise provided that special measures were not observed. It was suggested in [4] to divide open field image of interest into subdomains, deter mine mean brightness in subdomains, and calculate vari ance of mean brightness in subdomains. Mean brightness in subdomains is used to calculate system output noise variance.…”
Section: Estimate Of Scattering In Detector Channelsmentioning
confidence: 99%
“…Mean brightness in subdomains is used to calculate system output noise variance. The subdomains were suggested in [4] to be reduced to 16 elements (subdomain size, 4 × 4 pixels). However, further research into X ray digital detectors revealed that subdomain size of 4 × 4 pixels was insuffi cient (if noise correlation coefficient in neighboring chan nels is >0.2).…”
Section: Estimate Of Scattering In Detector Channelsmentioning
confidence: 99%
“…Substituting the obtained value of N into Eq. (2) we obtain a generalized formula for the signal/noise ratio for an ideal system of X ray detection: (4) Taking into account that the detective sensitivity is usually determined from the exposure dose D in the input plane, Eq. (4) can be rewritten as follows: D = 7.3⋅10 −9 ⋅(signal/noise) 2 ⋅E⋅µ a ⋅(pairs of lines/mm) 2 /K 2 .…”
mentioning
confidence: 99%
“…If this value cannot be attained at anode voltage of 70 kV (for example, if an automatic brightness stabilization system is used), the actual value of anode voltage and current and the thick ness of intrinsic and additional filters should be recorded in the protocol. 4. The resolution test object should be placed at the site of the patient.…”
mentioning
confidence: 99%